Exogenous surfactant therapy in non-respiratory distress syndrome - Greenough, Anne (The Turkish Journal of Pediatrics, 1996)
There is clinical evidence of the benefit of exogenous surfactant therapy to certain neonates with severe respiratory failure, diaphragmatic hernia, pneumonia and meconium aspiration syndrome. There still remain, however, important unanswered questions regarding, for example, optimum dosage and method of administration; appropriate randomized trials must be undertaken.
Keywords: surfactant replacement therapy; neonatal respiratory disorders